Is there a gender difference between ACE gene and race distance? - Min, S.-K.; Takahashi, K.; Ishigami, H.; Hiranuma, K.; Mizuno, M.; Ishii, T.; Kim, C.-S.; Nakazato, K. (Applied Physiology, Nutrition, and Metabolism, 2009)
We aimed to examine the association between the angiotensin I-converting enzyme (ACE) gene (insertion (I) and deletion (D)) polymorphism in Japanese university track athletes and race distance, as well as to evaluate the gender effects on this association. The ACE I/D allele frequency was determined in 277 athletes (176 men, 101 women; aged 19.7 ± 1.2 years), who were then grouped on the basis of their major competitive race distances (short distance (SD), </=200 m; middle distance (MD), 400-800 m, and long distance (LD), >/=1500 m). The ACE I allele frequency increased with the distance (44.4%, 48.4%, and 66.2% for the SD (n = 107), MD (n = 62), and LD (n = 108) groups, respectively; p < 0.001, x2 test). On multinomial logistic regression analysis, significant associations between ACE genotype and race distance were observed only in male athletes (ID vs. SD, p = 0.004; ID vs. LD, p = 0.030; II vs. LD, p = 0.001). There was no significant association between ACE genotype and race distance in female athletes. We conclude that the ACE I allele is overrepresented in endurance athletes, and that its frequency varies depending on gender.